Pharmacokinetic study of the prokinetic ABCs liquiritigenin, naringenin and hesperitin following the oral administration of Si–Ni–San decoction to functional dyspepsia patients. (3rd June 2019) - Huang, Xi; Xu, Jianjun; He, Juan; Shi, Shaoqi; Yan, Hongbin; Wang, Jian; Ren, Ping
Abstract: 1. The pharmacokinetics (PKs) analysis of compounds absorbed after the oral administration of Si-Ni-San (SNS) decoction to functional dyspepsia (FD) patients was designed to detect whether the effects were similar to prokinetics administered to healthy rats, without ethical limitation. 2. First, the absorbed compounds, liquiritigenin (L), naringenin (N) and hesperitin (H) in the plasma were identified by UPLC-MS/MS following the oral administration of SNS decoction to subjects with FD. Next, the natural ratio of LNH in the SNS decoction was determined by UPLC. Third, gastric emptying and intestinal transit after the oral administration of LNH, in combination or alone, was compared with those observed after SNS administration in healthy rats. Additionally, the clinical PKs of LNH was studied. 3. The prokinetic efficacy of LNH administered at their natural ratios (7.5:5:1) increased dose-dependently and was better than the observed efficacy when administered alone in rats. Analysis of the clinical PK parameters, calculated using a one-compartment model, showed that the C max parameters of LNH in 3, 4 and 4 h were 639.17, 410.00 and 181.67 μg/L, respectively. 4. The clinical herbal PK analysis of the absorbed LNH preclinical prokinetic compounds, in their natural ratio from SNS, highlights the impact of an herbal translational pharmacology study.